1973
DOI: 10.1139/p73-196
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a 1Δu1Σg+ Transition of CS2 in the Near Ultraviolet

Abstract: The strongest features of the gas-phase absorption spectrum of CS2 in the region 2900–3300 Å (Kleman's V system) are shown to belong to a 1B2–1Σg+ transition, where the 1B2 state correlates with the upper Renner–Teller component of the π → π* 1Δu state of the linear molecule. The barrier to linearity is about 1300 cm−1, and the structure of the molecule in the zero-point level is r(C–S) = 1.544 ± 0.006 Å, [Formula: see text]. Transitions to the lower Renner–Teller component, 1A2(1Δu), have been identified in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
1

Year Published

1978
1978
2004
2004

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(46 citation statements)
references
References 0 publications
4
41
1
Order By: Relevance
“…This R p l/Dl p 60,000 is much greater than the resolution of the CS 2 laboratory emis- The vacuum wavenumbers are from Kasahara et al (1984), except for those labeled with an asterisk, which are from Bernath et al (1981). c The assignments of the excited bands from which the emission lines have been observed are those reported by Ochi et al (1987), Jungen et al (1973), andKleman (1963).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…This R p l/Dl p 60,000 is much greater than the resolution of the CS 2 laboratory emis- The vacuum wavenumbers are from Kasahara et al (1984), except for those labeled with an asterisk, which are from Bernath et al (1981). c The assignments of the excited bands from which the emission lines have been observed are those reported by Ochi et al (1987), Jungen et al (1973), andKleman (1963).…”
Section: Resultsmentioning
confidence: 97%
“…There are many polyatomic molecules with strong bonding that undergo similar shifts, although they have not been as extensively studied in supersonic molecular beams as CS 2 . The near-ultraviolet spectroscopy (3800-2900 ; Kleman 1963;Jungen et al 1973;Ochi et A al. 1987) and the laser-excited fluorescence emission spectra of this molecule (Kasahara et al 1984;Bernath et al 1981;Silver & McKeever 1976;Dueñas Fañ anás & Cabello 1983;Lambert & Kimbel 1973;Matsuzaki et al 1982;Liou et al 1992;Vasudev 1982) have been investigated by many authors over the past 60 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 Baker et al 31 and Morgan et al 32 have studied the structure of CS 2 near 69 399 cm -1 Via two-photon and three-photon excitations. Specifically Morgan et al 32 have assigned a broad transition at 69414 cm -1 to linear 3 Π g Rydberg state, while higher resolution measurements of Baker et al 31 have observed transitions at energies of 69 330 cm -1 (peak E) assigned to the 3 Σ g -Rydberg state, 69 369 cm -1 (peak F, unassigned), 69 446 cm -1 (peak G) assigned to 1 Π g / 1 ∆ g Rydberg states, and the origin band (0 0 0 ) for a transition to a 1 Σ g + Rydberg state has been reported at 69 861 cm -1 .…”
Section: ∆Ementioning
confidence: 99%